Modeling intermittent cycling performance in hypoxia using the critical power concept - Townsend, N.; Shearman, S.; Skiba, P.; Dwyer, D. (Journal of Science and Cycling, 2015)
Purpose: Recently, a novel model derived from the critical power (CP) concept was developed to determine W`